2016
DOI: 10.1038/nrc.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

A panoply of errors: polymerase proofreading domain mutations in cancer

Abstract: Although it has long been recognized that the exonucleolytic proofreading activity intrinsic to the replicative DNA polymerases Pol δ and Pol ε is essential for faithful replication of DNA, evidence that defective DNA polymerase proofreading contributes to human malignancy has been limited. However, recent studies have shown that germline mutations in the proofreading domains of Pol δ and Pol ε predispose to cancer, and that somatic Pol ε proofreading domain mutations occur in multiple sporadic tumours, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
303
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(332 citation statements)
references
References 124 publications
(249 reference statements)
9
303
0
8
Order By: Relevance
“…This observation is important because it demonstrates that cancer cells do not need to inactivate both SAMHD1 alleles to increase the dNTP pools. Of note, the genes encoding Pol e and δ are examples of two other genes in which heterozygous mutations have recently been associated with human cancers (58). dNTP pool increases in SAMHD1 +/− mouse embryos are modest but significant and range from 20% to 60% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is important because it demonstrates that cancer cells do not need to inactivate both SAMHD1 alleles to increase the dNTP pools. Of note, the genes encoding Pol e and δ are examples of two other genes in which heterozygous mutations have recently been associated with human cancers (58). dNTP pool increases in SAMHD1 +/− mouse embryos are modest but significant and range from 20% to 60% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although some other driver mutations were also shared between the precursors and paired cancers (median of four shared mutations per pair, relative to a median of seven mutations per EIN and median of 10 mutations per carcinoma), the progression from EIN to malignancy was associated with both the loss (median of three mutations lost in carcinomas as compared with paired EINs) and, more frequently, gain (median of six mutations gained in carcinomas as compared with paired EINs) of driver mutations (Figure 1A,B; supplementary material, Table S7). Notably, many of the driver mutations gained were replacements of a glutamic acid or arginine codon with a nonsense codon (E → * or R → *), consistent with the characteristic mutational bias associated with POLE mutation (C:G → A:T transversions, in which the mutated cytosine is in the context T C T, and C:G → T:A transitions, in which the mutated cytosine is in the context T C G) 4, 5, 6 (Figure 1B; supplementary material, Table S7).…”
Section: Resultsmentioning
confidence: 72%
“…Dysfunction of the DNA repair system, however, can trigger the emergence of somatic mutations, resulting in enhanced genetic instability. In fact, several types of congenital and acquired human cancers contain mutations or exhibit methylated silencing of DNA repair genes, including MLH1 and polymerase e (POLE) [132,133]. We recently demonstrated that the expression level of MSH2, a representative mismatch repair protein, is downregulated by tumor necrosis factor-a in inflamed hepatocytes [134].…”
Section: Genetic Alterations Accumulated In Hepatitis Virusinfected Lmentioning
confidence: 99%